Impact of early enteral nutrition combined with fine nursing in patients with intracranial aneurysm undergoing minimally invasive surgery - Fu, Yujia; Xiong, Mengya; Zuo, Tian; Li, Yun; Wang, Ru; Wang, Dongmei (Frontiers in Surgery, 2026)
BackgroundPostoperative recovery in patients undergoing minimally invasive surgery for intracranial aneurysms is often hindered by delayed mobilization, inadequate nutritional support, and prolonged hospital stay. Conventional care using parenteral nutrition and standard nursing practices may not sufficiently address these issues. This study evaluated the combined effects of early enteral nutrition and enhanced nursing care on recovery outcomes.New methodA total of 138 patients were divided into a control group receiving standard nursing care and parenteral nutrition and an observation group receiving enhanced nursing care alongside early enteral nutrition. Recovery outcomes, including time to ambulation, gastrointestinal function recovery, hospital stay duration, pain levels, complication rates, nutritional and immune function, quality of life, and nursing satisfaction were assessed.ResultsThe observation group showed significantly earlier mobilization, faster gastrointestinal recovery, and shorter hospital stay than the control group. Pain levels and complication rates were lower, and nursing satisfaction was higher. Nutritional and immune markers and quality of life scores improved significantly in the observation group.ConclusionsEarly enteral nutrition combined with enhanced nursing care improves recovery, reduces complications, and enhances overall patient satisfaction, presenting an effective alternative to conventional care for patients undergoing intracranial aneurysm surgery.